Heat exchanger design in a hot-water store - Mote, R. T. (Cranfield University, 1991)
The behaviour of natural convective buoyancy-driven flows within a hot-water store due to the forced passage of colder water through the heat-exchanger's pipe are reviewed in the light of recent advances in experimental throughout the literature. The exchanger designs, for natural unworkable for the engineer complication arises because the heat exchanger are sensitive to and numerical studies, reported empirical development of heat convection problems, are often with a specification. The heat transfer performance of the the initial boundary conditions of the problem, ranging from the initial charged temperature of the water in the insulated tank of a fixed dimensíon, to the physical properties of the heat-exchanger's pipe. It was concluded that an improvement in the heat transfer performance can be derived by determining the optium length and the orientation of the heat-exchanger's arrangement. Further benefits are derived by correlating the thermal convective behaviour, within the hot-water store, with the forced passage of colder water through the heat exchanger's pipe. A convective flow model, based upon the experimental results, is described to advance the heat exchanger design principles in the situation of transient natural convection. Assumptions employed in the experimental work confirm that realistic and reasonable results can be obtained from the thermal analysis of the vertical cylindrícal store in two-dimensions.